Treatment of Proximal Humeral Fractures in Older Patients During COVID-19 Pandemic in Germany - Sußiek J; Koeppe J; Fischhuber K; Iking J; Marschall U; Raschke MJ; Katthagen JC; Stolberg-Stolberg J (Clinical Epidemiology)
Julia Sußiek,1,* Jeanette Koeppe,2,3,* Karen Fischhuber,2,3 Janette Iking,1,3 Ursula Marschall,4 Michael J Raschke,1 J Christoph Katthagen,1,3 Josef Stolberg-Stolberg1,3 1Department of Trauma-, Hand- and Reconstructive Surgery, University Hospital Muenster, Muenster, Germany; 2Institute of Biostatistics and Clinical Research, University of Muenster, Muenster, Germany; 3Research Group “Mathematical Surgery”, University Hospital Muenster, University of Muenster, Muenster, Germany; 4Department of Medicine and Health Services Research, BARMER Health Insurance, Wuppertal, Germany*These authors contributed equally to this workCorrespondence: Josef Stolberg-Stolberg, Department of Trauma-, Hand- and Reconstructive Surgery, University Hospital Muenster, Albert-Schweitzer-Campus 1, Building W1, Muenster, 48149, Germany, Tel +49 251 83 59231, Email josef.stolberg-stolberg@ukmuenster.dePurpose: The COVID-19 pandemic had a severe influence on the entire health sector. Until today, the effect of a SARS-CoV-2 infection on older patients with a proximal humeral fracture (PHF) is unknown. This study examined the following questions: Did the incidence of PHF of older people in Germany vary during the pandemic? Did the treatment change between the lockdown and non-lockdown periods? Was a SARS-CoV-2 infection associated with a worse outcome?Methods: Retrospective claims data of the BARMER health insurance were analysed. All in- and outpatient cases of insurance holders ≥ 65 years from 01/2010 to 09/2022, with coded diagnosis of PHF were analysed. Primary endpoints were the 1-month incidence of PHF per 100,000 insurance holders, number of operative therapies, in-hospital death and in-hospital major adverse events (MAEs).Results: 174,898 inpatient PHF cases were included. During the lockdown periods, the total incidence fell, while the outpatient incidence partially increased during the pandemic-period. Regarding the therapy allocation, there were no relevant persisting changes. In a detailed analysis of 23,979 PHF cases from 01/2020 to 09/2022, 4.1% patients suffered from a SARS-CoV-2 infection and showed a notably higher in-hospital mortality (8.1% vs 2.5%; risk adjusted OR 2.79, 95% CI 2.11– 3.70, p < 0.001) and more MAEs (17.0% vs 7.8%; risk adjusted OR 1.43, 95% CI 1.15– 1.77, p < 0.001).Conclusion: During the COVID-19 pandemic, the overall incidence of PHF in older patients was reduced. The treatment allocation did not change between the pre- and intra-pandemic period. An infection with SARS-CoV-2 was associated with higher mortality and more MAEs.Keywords: COVID-19, geriatric surgery, health service research, proximal humerus fracture